Altered expression of keratin 14 in lesional epidermis of autoimmune skin diseases - Wei, Xiaoying; Fricker, Katharina; Enk, Alexander; Hadaschik, Eva (International journal of dermatology, 2016)
Background Keratin 14 (K14) is an intermediate filament protein that is mainly expressed in the basal layer of healthy stratified epithelia. K14 has been identified as an autoantigen in the autoimmune-mediated skin disease of Scurfy mice and patients with the “immune dysregulation polyendocrinopathy, enteropathy, and X-linked” syndrome. Objectives To examine whether K14 is a target protein in autoimmune skin diseases (ASD), we analyzed the expression pattern of K14 in lesional skin of patients with lichen ruber, cutaneous lupus erythematosus, dermatomyositis, graft-versus-host disease, psoriasis, and pemphigus vulgaris, and evaluated the reactivity of patient sera with recombinantly expressed and epidermis-derived K14. Methods K14 expression was analyzed by immunohistochemistry on paraffin-embedded tissue sections of 17 healthy individuals and 58 patients with ASD. Sera from 10 healthy individuals and 41 patients with ASD were analyzed by Western blot for the presence of anti-K14 autoantibodies. Results In skin of patients with ASD, K14 expression is retained in suprabasal layers. In ASD with interface dermatitis, we observed focal loss of K14 within the basal layer and in hair follicles as well. A scattered dot-like K14 staining is seen in papillary dermis, most prominently in cutaneous lupus erythematosus and lichen ruber. Using Western blot, we show that sera of different patients with ASD recognize recombinantly expressed K14. Conclusion We show focal loss of K14 in the basal epidermis correlating with interface dermatitis and hair follicle involvement. Moreover, enhanced reactivity of sera of patients with atopic dermatitis with K14 suggests K14 may function as an autoantigen in ASD.
First published: 06 November 2015
Gesehen am 04.06.2020